ANALISIS YURIDIS PENGGUNAAN MATA UANG VIRTUAL (BITCOIN) SEBAGAI SARANA TINDAK PIDANA PENCUCIAN UANG (MONEY LAUNDERING) - Parwoto, Adi; Deliana, Evi; Ferawati, Ferawati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Rapid technological developments bring progress in almost all aspects of humanlife. In line with the development in this era of globalization, developed also economicactivities that occur in society. One means of payment that developed recently is virtualmoney. Virtual money then started to become a phenomenon in society since theemergence of crypto currency (Cryptocurrency) as a manifestation of technologicaldevelopments in e-commerce activities .. In Indonesia Bitcoin has also been growingvery rapidly, according to one of the exchanger (provider of exchange services, purchase, sending and receiving of Bitcoin) in Indonesia, namely PT.Bitcoin Indonesia through itsWeb page (indodax.com), during the period early 2015 to mid 2018,unfortunately, Along with the development of the virtual currency Bitcoin inIndonesia, there is no regulation governing the use and protection of the law against theBitcoin in Indonesia in eksplisitTidak any special arrangements to Bitcoin is certainly animpact on the users of Bitcoin itself, since Bitcoin itself is very vulnerable Cracking ofthe offenses, hacking and various cybercrime (cybercrime). EvenExecutive Director ofthe Communications Department of Bank Indonesia, Agusman as reported in a writtenstatement print media Tempo, Saturday, January 13, 2018 to give a statement that